In vivo protocol for testing efficacy of hand-washing agents against viruses and bacteria: experiments with rotavirus and Escherichia coli. - Ansari, S A (1989)
Ten antiseptic formulations, an unmedicated liquid soap, and tap water alone were compared for their capacities to eliminate human rotavirus from the finger pads of adult volunteers; three of the antiseptics, the soap, and the tap water alone were also tested against Escherichia coli. A fecal suspension of virus or bacterium was placed on each finger pad and air dried. The contaminated site was exposed to the test product for 10 s, rinsed in tap water, and dried on a paper towel. The residual virus or bacterium was then eluted. Selected agents were also tested by an analogous whole-hand method by which the entire palm surfaces of both hands were contaminated. Alcohols (70%) alone or with Savlon reduced the virus titer by greater than 99%, whereas the reductions by Proviodine, Dettol, and Hibisol ranged from 95 to 97%. Aqueous solutions of chlorhexidine gluconate were significantly less effective for virus removal or inactivation than 70% alcohol solutions. Furthermore, Savlon in water (1:200) was found to be much less effective in eliminating the virus (80.6%) than the bacterium (98.9%). The tap water alone and the soap reduced the virus titers by 83.6 and 72.5% and the bacterial titers by 90 and 68.7%, respectively. The results of the whole-hand method agreed well with those of the finger pad protocol. We conclude that the finger pad method is a suitable model for testing the in vivo efficacy of hand-washing agents and emphasize the need for using appropriate test viruses and bacteria.